Vivências compartilhadas de filhos separados pela hanseníase no RN a luz da história oral de vida - Cabral, Ana Michele de Farias (2013)
Several epidemics marked the lives of individuals and communities in all historical periods, and a prime example is leprosy, infectious disease marked by stigma, prejudice and social exclusion. In the past, the compulsory isolation of patients with leprosy caused serious social and psychological problems, resulting in the separation and the partial or total disruption of the family relationship. Children deprived of this living, removed often inhumanely, were kept and bred in preventoriums / educational establishments. This study aimed to: rescue the oral history of life of the children of leprosy patients that were built in preventorium Osvaldo Cruz, Natal, Rio Grande do Norte; develop a contextual analysis about these children; know the life trajectory of children of leprosy patients institutionalized in preventoriums / educational establishments; produce a documentary on the history of life of children of parents separated by leprosy; forming MORHAN of Rio Grande do Norte state; and implement the I Meeting of MORHAN of Rio Grande do Norte state. This is an exploratory and descriptive study, with a qualitative approach, approved by the ERC No. 024/024/2012 Liga Norteriograndense Contra o Câncer. We used the contributions of the method and technique of oral history of life as methodological reference. We interviewed 10 individuals egress from preventorium Osvaldo Cruz in Natal/RN, sons of former patients proven to be residents in the city, of both sexes, older than 18, with cognitive, intellectual and emotional conditions preserved. The analysis of the histories obtained from collaborators was performed in the light of Thematic Content Analysis. The results and discussions are presented through two articles which meet the proposed objectives. The first, called Contextual Analysis on the children of leprosy patients in preventoriums aimed to record the phenomenon of children of leprosy patients in preventorium through four contextual levels, which identified the need to broaden the debate on public policy in the field of leprosy as a way to enable more effective measures to propagate in the search for harm reduction and direct consequences resulting from stigma and marginalization around patients and their healthy children, egress from preventoriums. The second, Leprosy and the denial of history: the story of separated children , aimed to know the life trajectory of children of leprosy patients who were institutionalized in preventoriums / educational establishments. In this article, we discuss the research question through the establishment of three main themes: 1. Losses and damages: disintegration and reintegration into the family and denied childhood; 2. Unforgettable: remarkable things you do not forget; and 3. Expectancy in living new situations: in search of other paths and destinations. These thematic axis highlighted the negative implications for the lives of the subjects, arising from the separation of their parents, leprosy patients at the time of compulsory isolation; however, has also been shown that this separation was not decisive in their life histories, once they have succeeded in providing a new sense of these experiences and lead their lives with dignity and fortitude. It was concluded that these children demonstrated resilience as form of defense and fighting stigma and prejudice, being able to reinvent themselves and build new paths and destinations